Evaluation of Parents and Peers without Special Needs Roles in Sustaining Inclusive Practices in Enugu State, Nigeria - Okoroipa, Njideka Ifeoma; Ihenacho, Izuka John; Bodang, Juliana R.; Oluka, Beth Nnenne (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
This study evaluated the impact of roles of parents and peers without special needs (PWSN) in sustaining inclusive practices in Enugu state Nigeria: A pilot study report on â€œEvaluation of inclusive education practices for learners with special needs in primary schools in Enugu state of Nigeriaâ€. The study adopted a descriptive cross-sectional survey research design. Two research questions and one hypothesis guided the study. The population of the study comprised 351 teachers and 278 learners. A questionnaire named (IPPQ) was used to elicit responses from the respondents. Cronbachâ€™s Alpha method yielded a reliability index of 0.80. The research questions were analyzed using simple percentages, mean and standard deviation. The study found that (PWSN) to a moderate level, help and support their peers with special needs while mostly it is parents of learners with special needs who help and support inclusion. The study recommended along with others, the need to create awareness for inclusion among parents of learner without special needs. Keywords: Evaluation; inclusive practices, parents, peers without special needs; and primary schools .